Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How to solve system equation $\left\{\begin{matrix}x^3+y^3+z^3=x+y+z&\\x^2+y^2+z^2=xyz&\end{matrix}\right.$ , $x,y,z\in\mathbb{R}$ ?

share|improve this question
1  
What have you tried? –  Ahaan Rungta Oct 24 '13 at 15:05
    
I have tried so many times; but i couldn't find the solution –  Lê Tấn Khang Oct 24 '13 at 15:06

3 Answers 3

We'll using the follwoing notation:

$$s_1 = x + y + z$$ $$s_2 = x^2 + y^2 + z^2$$ $$s_3 = x^3 + y^3 + z^3$$

And we'll express $x,y,z$ as root of the cubic equation $f(x) = ax^3 + bx^2 + cx + d$

From the Vieta's formulas we know that $d = -xyz$

From the condition we have $d = - s_2$ and $s_1 = s_3$

Now use Newton's identitities and we have:

$$as_1 + b = 0$$

$$b = -as_1$$

Now repeat the process:

$$as_2 + bs_1 + 2c = 0$$ $$as_2 + -as_1^2 + 2c = 0$$ $$a(s_2 - s_1^2) + 2c = 0$$ $$2c = -a(s_2 - s_1^2)$$ $$c = \frac{-a(s_2 - s_1^2)}{2}$$

And one last time:

$$as_3 + bs_2 + cs_1 + 3d = 0$$ $$as_1 - as_1s_2 + \frac{-as_1(s_2 - s_1^2)}{2} - 3s_2 = 0$$ $$as_1\left( 1 - s_2 - \frac{s_2 - s_1^2}{2}\right) - 3s_2 = 0$$ $$as_1\left(\frac{-s_2 + s_1^2 + 2 - 2s_2}{2}\right) = 3s_2$$ $$a = \frac{6s_2}{s_1(-s_2 + s_1^2 + 2 - 2s_2)}$$

Now for arbitrary $s_1$ and $s_2$ you should be able to obtain a cubic equation, which roots will satisfy the condition.

share|improve this answer

Express all of the terms in terms of the symmetric polynomials $s_1=x+y+z, s_2=xy+yz+zx$ and $s_3=xyz$.

You get $s_1^3-3s_1s_2+3s_3=x^3+y^3+z^3=x+y+z=s_1$ and $s_1^2-2s_2=x^2+y^2+z^2=xyz=s_3$.

Putting the second equation into the first gives $s_1^3-3s_1s_2+3s_1^2-6s_2=s_1$, which simplifies to $s_2=(s_1^3+3s_1^2-s1)/(3s_1+6)$ and $s_3=s_1^2-2s_2$.

Then the solutions to the original equations are the roots of the polynomial $x^3-s_1x^2+s_2x-s_3$ where $s_2$ and $s_3$ are given according to the previous paragraph.

However, for almost all values of $s_1$, 2 of these roots are complex, so these are not real solutions.

In order to get real solutions, you need the discriminant of $x^3-s_1x^2+s_2x-s_3$ to be non-negative. This simplifies to $s_1^2(s_1+2)(648+536s_1+426s_1^2+117s_1^3+12s_1^4-6s1^5-6s1^6+s1^7)$ being non-positive, and the only $s_1$'s for which this is satisfied are $s_1=0$ ($x,y,z=0$) and $-2.16821<=s_1<-2$.

Example non-0 solution are the roots to $100x^3+210x^2-2023x-4487$

share|improve this answer
    
You might use a different unknown for the final equation, say $t$ instead of $x$. We know that the name of the unknown is mostly irrelevant, but since this can confuse readers, it's better sticking to distinct names. –  egreg Oct 25 '13 at 10:04

We can show that there is no solution for $x,y,z>0$. Firstly we have: $$ x^{2}+y^{2}+z^{2}=xyz \implies xyz\geq 3(xyz)^{\frac 23}\\ \implies xyz\geq 27. $$ On the other hand we have: $$ x^{2}+y^{2}+z^{2}=xyz\geq \frac 13(x+y+z)^{2}=\frac 13(x^3+y^3+z^3)^{2}\geq \frac 13(3xyz)^{2}=3(xyz)^2\\ xyz\leq \frac 13 $$ So we have $xyz\leq \frac 13$ and $xyz\geq 27$ which is a contradiction and hence there is no solution for positive $x,y,z$.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.